The impact of customer relationship management practice on customer loyalty (specific reference to local commercial banking sector in jaffna district) - Umakanth, N. (university of Jaffna, 2014)
Managing effective Relationship Marketing Practices are increasingly important in the banking industry. Since the length in years of customer relationships are one of the most important factors that contribute to the profitability. As a result Customer Satisfaction may be one important driver of Customer Retention The goal of this research project is identify and assess impact relationship marketing practice on loyalty in local commercial banking sector in Jaffna. The research was mainly based on data, collected from customers in Jaffna commercial banks. Quantitative methodology has been applied and questionnaire was used to collect data, descriptive statistics as well as inferential statistical analysis using SPSS. 17.0 household customers have been selected from 34 licensed commercial banks that comprised of public and private bank. Multiple regression has been used for the analysis .The results of the statistical analysis showed that is a strong positive impact of relationship marketing practices on customer on Loyalty. Therefore these findings will help the banks to establish a customer oriented strategy to retain their customers in future.
Keywords: Relationship marketing; Customer loyalty; Banking sector; Sri lanka